A COMPARATIVE ANALYSIS OF PRESENT SIMPLE, PAST SIMPLE, AND FUTURE SIMPLE IN ENGLISH AND FRENCH - Ruzieva Nasiba Kenjaevna,; G'ayvullayeva Jasmina , (TADQIQOTLAR.UZ, 2023)
The present simple, past simple, and future simple are fundamental tenses in both English and French, serving as the cornerstones of grammatical expression. Despite their shared purpose, these tenses exhibit distinct nuances and applications in each language. This comparative analysis delves into the intricacies of these tenses, highlighting their similarities and dissimilarities between English and French.